Quantitative analysis method for asphalt mixture interface adhesion performance based on three-dimensional scanning
By combining three-dimensional scanning technology with the boiling or immersion method, the problem of quantitative analysis of interfacial adhesion properties of asphalt mixtures has been solved, enabling reliable assessment of the quality of asphalt pavement materials and improving the accuracy and applicability of the evaluation.
Patent Information
- Application Number
- CN202511817400.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-02-06
AI Technical Summary
In the existing technology, the quantitative analysis method for the interfacial adhesion performance of asphalt mixtures has the problems of complicated operation, the results being greatly affected by human factors, and difficulty in being effectively applied in engineering practice.
Using 3D scanning technology combined with boiling or immersion methods, high-density point cloud data of asphalt-aggregate mixtures are acquired through a non-contact 3D laser scanner. After processing with reverse engineering software, the volume ratios R1 and R2 are calculated to quantitatively evaluate the adhesion performance between asphalt and aggregates.
It enables precise quantitative analysis of the interfacial adhesion properties of asphalt mixtures, reduces the influence of human factors, and improves the accuracy and reliability of evaluation. It is applicable to the quality inspection and engineering characteristic assessment of asphalt pavement materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a quantitative analysis method for the interfacial adhesion properties of asphalt mixtures based on three-dimensional scanning, belonging to the field of building materials technology. Background Technology
[0002] Asphalt, as a crucial geosynthetic material, is widely used in road engineering and building waterproofing projects. Asphalt pavement is a primary pavement structure in highways; almost all completed and under-construction expressways in my country utilize asphalt concrete pavement. Asphalt pavement is constructed from asphalt mixtures, with asphalt acting as a binder to bind mineral aggregates of a specific gradation into a cohesive whole to jointly bear the pavement load. The interfacial phase, distinct from the aggregate-asphalt composite, is formed at the interface between the mineral aggregates and asphalt due to complex physicochemical reactions between them. The interfacial phase interaction between aggregates and asphalt is extremely important; research indicates that the strength of the interfacial phase between asphalt and aggregates is key to influencing the quality stability of asphalt mixtures. However, early damage to asphalt pavements is quite severe in some areas. Often, asphalt peeling, potholes, and other defects appear after only two or three years of operation. These defects are closely related to the adhesion properties between asphalt and aggregates. Therefore, it is particularly important to conduct in-depth research on the adhesion properties of asphalt, understand the adhesion mechanism between asphalt and aggregates, and propose a more reliable scientific evaluation index for the quality inspection and engineering characteristic assessment of asphalt pavement materials in practical engineering. This is of great significance for reducing early defects of asphalt pavements, improving the driving quality of asphalt pavements, and even improving the economic efficiency of construction.
[0003] Domestic and international research often employs methods such as boiling water, immersion water, and photoelectric colorimetry to qualitatively or semi-quantitatively evaluate the adhesion performance of asphalt mixtures. Each of these methods has its advantages and disadvantages. Boiling water and immersion water are commonly used evaluation methods in engineering practice. These two methods are simple, fast, and widely applicable, capable of qualitatively and semi-quantitatively evaluating the adhesion between asphalt and aggregates. However, the asphalt adhesion grade often requires experienced researchers to determine it through visual observation, and the resulting asphalt adhesion grade is significantly influenced by subjective factors, making quantitative characterization difficult. Therefore, the industry urgently needs a simple, fast, and practical quantitative analysis method for the interfacial adhesion performance of asphalt mixtures. Summary of the Invention
[0004] The purpose of this invention is to provide a quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning, so as to solve the defects of the current boiling water method and water immersion method in adhesion evaluation, and to provide a more reliable scientific evaluation index for the quality inspection and engineering characteristic evaluation of asphalt pavement materials in engineering practice.
[0005] The technical solution of this invention is: A quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning includes three-dimensional scanning of the original aggregate, three-dimensional scanning of the asphalt-aggregate mixture, three-dimensional scanning of the asphalt-aggregate mixture after boiling or immersion tests, and volumetric data processing. The specific steps are as follows: A. Three-dimensional scanning of the test raw aggregate; A.1 Take a number of regularly shaped aggregates with a particle size of 9.5mm~19mm, wash them with pure water, dry them in an oven at a temperature of 105℃±5℃, and use a non-contact 3D laser scanner to scan the aggregate particles to obtain high-density point cloud data that reflects the surface feature information of the aggregates. A.2 The high-density point cloud data was processed by the reverse engineering software Geomagic Wrap, which performed noise reduction, sampling, encapsulation, filling, sharpening and fitting. The boundary lines and point clouds were used to fit the surface model of the aggregate, which was then numbered and stored in the database. The surface model fitted by the aggregate was spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the aggregate in the global coordinate system was calculated. After obtaining the accurate three-dimensional coordinates of the aggregate surface model, the volume data of the surface model was extracted and denoted as V1. B. Three-dimensional scanning of asphalt-aggregate mixtures; B.1 Asphalt-aggregate mixtures were prepared using raw aggregates and asphalt. A non-contact 3D laser scanner was used to perform 3D scanning of the asphalt-aggregate mixtures to obtain high-density point cloud data reflecting the surface feature information of the asphalt-aggregate mixtures. B.2 As described in step (A.2), the high-density point cloud data is processed by noise reduction, sampling, encapsulation, filling, sharpening and fitting using the reverse engineering software Geomagic Wrap. A surface model is fitted with the boundary lines and the point cloud, numbered and stored in the database. The fitted surface model is then spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data in the global coordinate system is calculated to obtain the precise three-dimensional coordinates of the material surface model. The volume data of the surface model is then extracted and denoted as V2. C. After the mixture is subjected to boiling or immersion tests, a three-dimensional scan is performed. The scanning method is the same as in step B. The volume data of the surface model of the material is recorded as V3. D. Data processing and computation; By comparing the obtained volumes V1, V2, and V3, the volume ratios R1 = V3 / V2 and R2 = V3 / V1 are obtained. Based on the different volume ratios, the asphalt adhesion is divided into five levels, thereby effectively evaluating the interfacial adhesion performance of asphalt-aggregate mixtures. This invention directly evaluates the adhesion performance between asphalt and aggregates based on the volume ratios R1 and R2, and quantitatively evaluates the variation law of asphalt adhesion performance. When R1≥98% and R2≥1, the adhesion grade is 5, the asphalt has excellent complete adhesion, and the asphalt is suitable as a binder for preparing asphalt-aggregate mixtures; When 85%≤R1<98% and R2≥1, the adhesion grade is 4, indicating good complete adhesion of asphalt and that asphalt is suitable as a binder for preparing asphalt-aggregate mixtures. When 60%≤R1<85% and R2≥1, the adhesion grade is 3, the asphalt adhesion is generally good, and asphalt can be used as a binder to prepare asphalt-aggregate mixtures. When 30%≤R1<60% and R2≥1, the adhesion grade is 2, the asphalt has poor complete adhesion, and asphalt is not recommended to be used as a binder in the preparation of asphalt-aggregate mixtures. When R1 < 30% and R2 ≥ 1, the adhesion grade is 1, the asphalt has extremely poor adhesion, and the asphalt is not suitable as a binder for preparing asphalt-aggregate mixtures. When R2 < 1, the experimental data is considered invalid because the equipment precision error or the chemical reaction between the aggregate and water makes it impossible to evaluate the complete adhesion of the asphalt, and thus the adhesion grade cannot be obtained.
[0006] The method for preparing asphalt-aggregate mixtures using raw aggregates and asphalt includes the boiling method or the immersion method. The boiling method involves tying the weighed aggregate in the middle of a cotton thread, immersing it in a preheated asphalt sample until the aggregate particles are completely coated with an asphalt film, then suspending the cotton thread vertically on a test stand at room temperature. The mixture is allowed to drip clean and cool for 15 minutes to obtain the asphalt-aggregate mixture. The immersion method involves placing the weighed aggregate particles in an enamel pan, and then placing the pan and the mixture in an oven heated to 5°C above the asphalt mixing temperature for 1 hour. The mixture is prepared by mixing 100... Weigh out asphalt to an accuracy of 0.1g, adding 5.5g ± 0.2g of aggregate to the asphalt mixture. Place the asphalt in a mixer and heat in an oven at 130-150℃ for 15 minutes. Pour the aggregate from the enamel pan into the asphalt in the mixing container and immediately mix evenly with a metal shovel for 1-1.5 minutes to ensure the aggregate is completely coated with an asphalt film. Then, immediately transfer the asphalt-coated aggregate to a glass plate with a metal shovel and spread it out. Allow it to cool at room temperature for 1 hour to obtain the asphalt-aggregate mixture. Generally, materials with a particle size between 13.2-19mm are boiled in water, while materials with a particle size below 13.2mm are soaked in water.
[0007] The specific steps of the boiling or immersion test for asphalt-aggregate mixtures are as follows: Immerse the asphalt-aggregate mixture in a beaker containing boiling salt water with a concentration of 1g / 100mL. Adjust the temperature of the electric heater to keep the water in the beaker at a gentle boil without boiling bubbles. After boiling for 3 minutes, remove the asphalt-aggregate mixture from the water and suspend it vertically on the test rack with a cotton thread. Allow it to cool at room temperature until the surface moisture of the asphalt-aggregate mixture is naturally air-dried. The specific steps of the immersion test are as follows: Immerse a glass plate containing the asphalt-aggregate mixture in a constant temperature water bath at 80℃±1℃ for 30 minutes. Use paper to remove the asphalt that has peeled off and floated on the water surface. Finally, carefully remove the glass plate from the water and immerse it in cold water in the water bath. After standing for 15 minutes, remove it and allow it to cool at room temperature until the surface moisture of the asphalt-aggregate mixture is naturally air-dried. Generally, materials with a particle size between 13.2-19mm are treated with the boiling method, while materials with a particle size below 13.2mm are treated with the immersion method.
[0008] The beneficial effects of this invention are: 1. The non-contact 3D laser scanner used in this invention adopts advanced optical-mechanical precision machining technology and laser projection structured light, which can complete the acquisition of a large amount of material data in a short time, making the volume calculation results more accurate and faster.
[0009] 2. In this invention, the asphalt film peeling degree on the aggregate surface obtained by boiling or immersion in water is calculated by reverse engineering software, which avoids contact with and possible damage to the tested material and eliminates the interference of human factors on the adhesion grade evaluation.
[0010] 3. This invention can accurately measure the actual conditions of materials and effectively study the interfacial adhesion performance of asphalt-aggregate mixtures.
[0011] 4. This invention is applicable to the quality inspection and engineering characteristic evaluation of various asphalt pavement materials, and has a wide range of applications. Attached Figure Description
[0012] Figure 1 This is a flowchart of the invention; Figure 2 This is a schematic diagram of the water boiling method test process of the present invention; Figure 3 This is a schematic diagram of the water immersion test process of the present invention. Detailed Implementation
[0013] This invention provides a quantitative analysis method for the interfacial adhesion properties of asphalt-aggregate mixtures based on three-dimensional scanning, such as... Figure 1As shown, the invention includes three-dimensional scanning of the original aggregate, preparation and three-dimensional scanning of the asphalt-aggregate mixture, water boiling or water immersion test of the asphalt-aggregate mixture, and three-dimensional scanning and volume data processing of the asphalt mixture after the test. The invention will be further described below with reference to specific embodiments, but the content of the invention is not limited to the embodiments described.
[0014] Example 1 A quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning was proposed. The raw aggregate used in this experiment was limestone. AC-16C asphalt mixtures were prepared by sieving the aggregates through 13.2mm and 19mm standard sieves. Materials with particle sizes between 13.2-19mm were selected for testing using a water boiling method. Figure 2 As shown, perform the following steps: A. Three-dimensional scanning of the test raw aggregate; A.1 Several selected aggregates were washed with pure water and dried in an oven at 105℃±5℃. The aggregate particles were scanned using a non-contact 3D laser scanner to obtain high-density point cloud data reflecting the surface features of the aggregates. A.2 The reverse engineering software Geomagic Wrap was used to perform noise reduction, sampling, encapsulation, filling, sharpening and fitting on the 3D point cloud data. The boundary lines and point clouds were used to fit the surface model of the aggregate, which was numbered 1.1, 1.2, 1.3... and then stored in the database. The surface model fitted by the aggregate was spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the aggregate in the global coordinate system was calculated. After obtaining the accurate 3D coordinates of the aggregate surface model, the volume data of the surface model was extracted and denoted as V1. B. Preparation of asphalt-aggregate mixture: Weigh the aggregate, tie it in the middle, attach it to the end of the cotton thread, immerse it in the asphalt sample that has been preheated to 140°C for 45 seconds, so that the aggregate particles are completely covered by the asphalt film, gently lift it out, hang the cotton thread vertically on the table on the test frame, let it drip clean at room temperature and cool for 15 minutes to obtain the asphalt-aggregate mixture. C. Three-dimensional scanning of asphalt-aggregate mixtures; C.1 A non-contact 3D laser scanner is used to perform 3D scanning on the precast asphalt-aggregate mixture to obtain high-density point cloud data that reflects the surface feature information of the mixture; C.2 The reverse engineering software Geomagic Wrap is used to perform noise reduction, sampling, encapsulation, filling, sharpening and fitting on the 3D point cloud data. The boundary lines and point clouds are used to fit the surface model of the aggregate, which is numbered 2.1, 2.2, 2.3... and then stored in the database. The fitted surface model is spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the material in the global coordinate system is calculated to obtain the accurate 3D coordinates of the material surface model. The volume data of the surface model is then extracted and denoted as V2. D. Conduct a boiling water test on the asphalt-aggregate mixture. Immerse one asphalt-aggregate mixture in the center of a beaker containing boiling salt water with a concentration of 1g / 100mL. Adjust the temperature of the electric heater to keep the water in the beaker at a gentle boil without boiling bubbles. After immersion for 3 minutes, remove the mixture from the water and let it stand at room temperature for 10 minutes. Then place it in a beaker containing room temperature water. Observe the degree of asphalt film peeling off the aggregate particles in the water. After visual evaluation by two or more experienced testers, take the average grade as the test result according to the adhesion rating grade of the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). Meanwhile, the asphalt-aggregate mixture (another one) was immersed in the center of a beaker containing boiling salt water with a concentration of 1g / 100mL. The temperature of the electric furnace was adjusted to keep the water in the beaker at a gentle boil without boiling bubbles. After immersion for 3 minutes, the mixture was removed from the water and left to stand at room temperature for 10 minutes. Then, the cotton thread was hung vertically on the test rack and left to stand at room temperature until the surface moisture of the mixture was naturally air-dried. E. Three-dimensional scanning of the asphalt-aggregate mixture after the test; E.1 A non-contact 3D laser scanner was used to perform a 3D scan on the asphalt-aggregate mixture after the test in step D to obtain high-density point cloud data reflecting the surface characteristics of the mixture; E.2 The reverse engineering software Geomagic Wrap is used to perform noise reduction, sampling, encapsulation, filling, sharpening and fitting on the 3D point cloud data. The boundary lines and point clouds are used to fit the surface model of the aggregate, which is numbered 3.1, 3.2, 3.3... and then stored in the database. The fitted surface model is spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the material in the global coordinate system is calculated to obtain the accurate 3D coordinates of the material surface model. The volume data of the surface model is then extracted and denoted as V3. F. Volume data processing; comparing the obtained volumes V1, V2, and V3 to obtain volume ratios R1 = V3 / V2 and R2 = V3 / V1; based on different volume ratios, asphalt adhesion is divided into five levels, thereby effectively evaluating the interfacial adhesion performance of asphalt-aggregate mixtures. This invention directly evaluates the adhesion performance between asphalt and aggregates based on volume ratios R1 and R2, and quantitatively evaluates the variation law of asphalt adhesion performance: When R1≥98% and R2≥1, the adhesion grade is 5, the asphalt has excellent complete adhesion, and the asphalt is suitable as a binder for preparing asphalt-aggregate mixtures; When 85%≤R1<98% and R2≥1, the adhesion grade is 4, indicating good complete adhesion of asphalt and that asphalt is suitable as a binder for preparing asphalt-aggregate mixtures. When 60%≤R1<85% and R2≥1, the adhesion grade is 3, the asphalt adhesion is generally good, and asphalt can be used as a binder to prepare asphalt-aggregate mixtures. When 30%≤R1<60% and R2≥1, the adhesion grade is 2, the asphalt has poor complete adhesion, and asphalt is not recommended to be used as a binder in the preparation of asphalt-aggregate mixtures. When R1 < 30% and R2 ≥ 1, the adhesion grade is 1, the asphalt has extremely poor adhesion, and the asphalt is not suitable as a binder for preparing asphalt-aggregate mixtures. When R2 < 1, the experimental data is considered invalid because the equipment precision error or the chemical reaction between the aggregate and water makes it impossible to evaluate the complete adhesion of the asphalt, and thus the adhesion grade cannot be obtained.
[0015] Comparing the adhesion grade obtained by the experimenter's visual inspection in step D with the adhesion grade obtained at the end of this embodiment, it can be found that the final method of the embodiment is somewhat similar to the conclusion of the manual visual inspection method. However, the final method of the embodiment has a higher accuracy rate. Manual visual inspection involves more uncertainties due to human involvement. This method does not require "experienced" experimenters, so the threshold for calculating the adhesion grade is lower and it is more convenient for practical engineering applications.
[0016] Example 2 A quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning was proposed. The aggregate used in this experiment was limestone, and AC-16C asphalt mixtures were prepared. The selected aggregates were sieved through 9.5mm and 13.2mm standard sieves. Materials with a particle size below 13.2mm were selected for water immersion adhesion testing. Figure 3 As shown, perform the following steps: A. Three-dimensional scanning of the test raw aggregate; A.1 Selected aggregates were washed with pure water, dried in an oven at 105℃±5℃, and then the aggregates were spread out on a glass plate with a metal shovel. A non-contact 3D laser scanner was used to scan the aggregate particles to obtain high-density point cloud data reflecting the surface features of the aggregates. A.2 The reverse engineering software Geomagic Wrap was used to perform noise reduction, sampling, encapsulation, filling, sharpening and fitting on the 3D point cloud data. The boundary lines and point clouds were used to fit the surface model of the aggregate, which was numbered 1.1, 1.2, 1.3... and then stored in the database. The surface model fitted by the aggregate was spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the aggregate in the global coordinate system was calculated. After obtaining the accurate 3D coordinates of the aggregate surface model, the volume data of the surface model was extracted and denoted as V1. B. Preparation of asphalt-aggregate mixture: Place the weighed aggregate particles in an enamel pan, and put the pan and the mixture into an oven (150°C) heated to 5°C above the asphalt mixing temperature for 1 hour. Weigh asphalt to the nearest 0.1g according to the ratio of 5.5g ± 0.2g of asphalt per 100g of aggregate, put it into a small mixer, and put it into the same oven (150°C) for 15 minutes. Pour the aggregate from the enamel pan into the asphalt in the mixing container, and immediately mix it evenly with a metal shovel for 1 minute to 1.5 minutes to ensure that the aggregate is completely coated with an asphalt film. Then immediately transfer the asphalt-coated aggregate to a glass plate with a metal shovel and spread it out. Cool it at room temperature for 1 hour to obtain the asphalt-aggregate mixture. C. Three-dimensional scanning of asphalt-aggregate mixtures; C.1 A non-contact 3D laser scanner is used to perform 3D scanning on the precast asphalt-aggregate mixture to obtain high-density point cloud data that reflects the surface feature information of the mixture; C.2 The reverse engineering software Geomagic Wrap is used to perform noise reduction, sampling, encapsulation, filling, sharpening and fitting on the 3D point cloud data. The boundary lines and point clouds are used to fit the surface model of the aggregate, which is numbered 2.1, 2.2, 2.3... and then stored in the database. The fitted surface model is spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the material in the global coordinate system is calculated to obtain the accurate 3D coordinates of the material surface model. The volume data of the surface model is then extracted and denoted as V2. D. Conduct a water immersion test on the asphalt-aggregate mixture; immerse a glass plate containing the asphalt-aggregate mixture in a constant temperature water bath at 80℃±1℃ for 30 minutes, and use paper to remove the peeled and floating asphalt. Finally, carefully remove the glass plate from the water and immerse it in cold water in the water bath. Carefully observe the peeling of the asphalt film covering the aggregate. After visual evaluation by two or more experienced testers, take the average grade as the test result according to the adhesion rating of the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). After evaluation, remove the glass plate and let it stand at room temperature until the surface moisture of the mixture dries naturally. E. Three-dimensional scanning of the asphalt-aggregate mixture after the test; E.1 A non-contact 3D laser scanner was used to perform a 3D scan on the asphalt-aggregate mixture after the test to obtain high-density point cloud data reflecting the surface characteristics of the mixture; E.2 The reverse engineering software Geomagic Wrap is used to perform noise reduction, sampling, encapsulation, filling, sharpening and fitting on the 3D point cloud data. The boundary lines and point clouds are used to fit the surface model of the aggregate, which is numbered 3.1, 3.2, 3.3... and then stored in the database. The fitted surface model is spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the material in the global coordinate system is calculated to obtain the accurate 3D coordinates of the material surface model. The volume data of the surface model is then extracted and denoted as V3. F. Volume data processing; comparing the obtained volumes V1, V2, and V3 to obtain volume ratios R1 = V3 / V2 and R2 = V3 / V1; based on different volume ratios, asphalt adhesion is divided into five levels, thereby effectively evaluating the interfacial adhesion performance of asphalt-aggregate mixtures. This invention directly evaluates the adhesion performance between asphalt and aggregates based on volume ratios R1 and R2, and quantitatively evaluates the variation law of asphalt adhesion performance: When R1≥98% and R2≥1, the adhesion grade is 5, the asphalt has excellent complete adhesion, and the asphalt is suitable as a binder for preparing asphalt-aggregate mixtures; When 85%≤R1<98% and R2≥1, the adhesion grade is 4, indicating good complete adhesion of asphalt and that asphalt is suitable as a binder for preparing asphalt-aggregate mixtures. When 60%≤R1<85% and R2≥1, the adhesion grade is 3, the asphalt adhesion is generally good, and asphalt can be used as a binder to prepare asphalt-aggregate mixtures. When 30%≤R1<60% and R2≥1, the adhesion grade is 2, the asphalt has poor complete adhesion, and asphalt is not recommended to be used as a binder in the preparation of asphalt-aggregate mixtures. When R1 < 30% and R2 ≥ 1, the adhesion grade is 1, the asphalt has extremely poor adhesion, and the asphalt is not suitable as a binder for preparing asphalt-aggregate mixtures. When R2 < 1, the experimental data is considered invalid because the equipment precision error or the chemical reaction between the aggregate and water makes it impossible to evaluate the complete adhesion of the asphalt, and thus the adhesion grade cannot be obtained.
[0017] Comparing the adhesion grade obtained by the experimenter's visual inspection in step D with the adhesion grade obtained at the end of this embodiment, it can be found that the final method of the embodiment is somewhat similar to the conclusion of the manual visual inspection method. However, the final method of the embodiment has a higher accuracy rate. Manual visual inspection involves more uncertainties due to human involvement. This method does not require "experienced" experimenters, so the threshold for calculating the adhesion grade is lower and it is more convenient for practical engineering applications.
[0018] The specific embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.
Claims
1. A quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning, characterized in that, The specific steps are as follows: A. Three-dimensional scanning of the test raw aggregate; A.1 Take aggregates with a particle size of 9.5mm~19mm, wash them with pure water and dry them. Use a non-contact 3D laser scanner to scan the aggregate particles and obtain high-density point cloud data of the material. A.2 The high-density point cloud data was processed by the reverse engineering software Geomagic Wrap, which performed noise reduction, sampling, encapsulation, filling, sharpening and fitting. The boundary lines and point clouds were used to fit the surface model of the aggregate, which was then numbered and stored in the database. The surface model fitted by the aggregate was spatially translated and rotated using the model editing software Materialise Magics. The corresponding contour point cloud data of the aggregate in the global coordinate system was calculated. After obtaining the accurate three-dimensional coordinates of the aggregate surface model, the volume data of the surface model was extracted and denoted as V1. B. Three-dimensional scanning of asphalt-aggregate mixtures; B.1 Asphalt-aggregate mixtures were prepared using raw aggregates and asphalt. A non-contact 3D laser scanner was used to perform 3D scanning of the asphalt-aggregate mixtures to obtain high-density point cloud data reflecting the surface feature information of the asphalt-aggregate mixtures. B.2 The high-density point cloud data was processed by the reverse engineering software Geomagic Wrap, which performed noise reduction, sampling, encapsulation, filling, sharpening and fitting. The boundary lines and point clouds were fitted to form a surface model, which was then numbered and stored in the database. The fitted surface model was then translated and rotated in space using the model editing software Materialise Magics. The corresponding contour point cloud data in the global coordinate system was calculated to obtain the accurate three-dimensional coordinates of the material surface model. The volume data of the surface model was then extracted and denoted as V2. C. After conducting a boiling or immersion test on the asphalt-aggregate mixture, perform a three-dimensional scan using the same method as in step B. The volume data of the material surface model obtained is denoted as V3. D. Data processing and computation; By comparing the obtained volumes V1, V2, and V3, the volume ratios R1 = V3 / V2 and R2 = V3 / V1 were obtained. Based on the different volume ratios, the asphalt adhesion was divided into five levels to quantitatively evaluate the interfacial adhesion performance of the asphalt-aggregate mixture. When R1≥98% and R2≥1, the adhesion grade is 5, the asphalt has excellent complete adhesion, and the asphalt is suitable as a binder for preparing asphalt-aggregate mixtures; When 85%≤R1<98% and R2≥1, the adhesion grade is 4, indicating good complete adhesion of asphalt and that asphalt is suitable as a binder for preparing asphalt-aggregate mixtures. When 60%≤R1<85% and R2≥1, the adhesion grade is 3, the asphalt adhesion is generally good, and asphalt can be used as a binder to prepare asphalt-aggregate mixtures. When 30%≤R1<60% and R2≥1, the adhesion grade is 2, the asphalt has poor complete adhesion, and asphalt is not recommended to be used as a binder in the preparation of asphalt-aggregate mixtures. When R1 < 30% and R2 ≥ 1, the adhesion grade is 1, the asphalt has extremely poor adhesion, and the asphalt is not suitable as a binder for preparing asphalt-aggregate mixtures. When R2 < 1, the experimental data is considered invalid because the equipment precision error or the chemical reaction between the aggregate and water makes it impossible to evaluate the complete adhesion of the asphalt and thus impossible to determine the adhesion grade.
2. The quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning according to claim 1, characterized in that, Methods for preparing asphalt-aggregate mixtures from raw aggregates and asphalt include boiling in water or soaking in water. The steps of the boiling method are as follows: the weighed aggregate is tied in the middle and tied to the end of the cotton thread. It is then immersed in the preheated asphalt sample so that the aggregate particles are completely covered by the asphalt film. The cotton thread is then suspended vertically on the test frame and allowed to drip clean at room temperature. After cooling for 15 minutes, the asphalt-aggregate mixture is obtained. The water immersion method is as follows: Place the weighed aggregate particles in an enamel pan, and heat the pan together to 5°C above the asphalt mixing temperature for 1 hour; weigh out asphalt at a ratio of 5.5g asphalt per 100g aggregate, put it into a mixer, and heat it at 130-150°C for 15 minutes; pour the aggregate from the enamel pan into the asphalt in the mixer, mix for 1-1.5 minutes to ensure that the aggregate is completely coated with an asphalt film, and then immediately transfer the asphalt-coated aggregate to a glass plate, spread it out, and cool it at room temperature for 1 hour to obtain an asphalt-aggregate mixture.
3. The quantitative analysis method for the interfacial adhesion performance of asphalt-aggregate mixtures based on three-dimensional scanning according to claim 1, characterized in that, The specific steps of the boiling or immersion test for asphalt-aggregate mixtures are as follows: Immerse the asphalt-aggregate mixture in boiling salt water with a concentration of 1g / 100mL. The water should be kept at a gentle boil without any boiling bubbles. After immersion for 3 minutes, remove the asphalt-aggregate mixture from the water and suspend it on the test rack with a cotton thread perpendicular to the table. Allow it to cool at room temperature until the surface moisture of the asphalt-aggregate mixture is naturally air-dried. The specific steps of the immersion test are as follows: Immerse a glass plate containing the asphalt-aggregate mixture in a constant temperature water bath at 80℃ for 30 minutes. Use paper to remove any asphalt that has peeled off or floated on the water surface. Finally, remove the glass plate from the water and immerse it in cold water. After standing for 15 minutes, remove it and allow it to cool at room temperature until the surface moisture of the asphalt-aggregate mixture is naturally air-dried.
Citation Information
Patent Citations
Quantitative analysis device for asphalt mixture interface adhesion performance based on three-dimensional scanning
CN223244386U
